Numerical analysis of wireless power transfer in near-field UHF-RFID systems. Issue 1 (27th November 2017) - Buffi, Alice; Michel, Andrea; Nepa, Paolo; Manara, Giuliano
Abstract : A preliminary numerical analysis of the power transfer efficiency (PTE) for the forward link of near-field (NF) ultra high frequency (UHF)-radio frequency identification (RFID) systems is addressed in this paper, by resorting to an impedance matrix approach where the matrix entries are determined through full-wave simulations. The paper is aimed to quantify the NF-coupling effects on the PTE, as a function of the distance between the reader and tag antennas. To allow for a PTE comparison between different reader and tag antenna pairs, a benchmarking tag-loading condition has been assumed, where the tag antenna is loaded with the impedance that maximizes the PTE. In a more realistic loading condition, the load impedance is assumed as equal to the conjugate of the tag antenna input impedance. Full-wave simulations use accurate antenna models of commercial UHF-RFID passive tags and reader antennas. Finally, a "shape-matched antenna" configuration has been selected, where the reader antenna is assumed as identical to the tag antenna. It is shown that the above configuration could be a valuable compact solution, at least for those systems where the relative orientation/position between the tag and reader antennas can be controlled, and their separation is of the order of a few centimeters or less.